Comparison of the effect of a period of physical fitness training with and without transcranial direct current stimulation (tDCS) on decision-making and pistol shooting performance - Esmaieli, M.; Rahimzadeh, M.; Karami, E. (EBNESINA, 2024)
Background and aims: Complete combat readiness is an emerging concept in the 21st century that is achieved by integrating mental and physical components. This study aimed to compare the effects of a period of physical fitness training with and without transcranial direct current stimulation (tDCS) on decision-making and pistol shooting performance among officer students.